2016
DOI: 10.4236/gep.2016.44014
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multivariate Geostatistics in Environmental Epidemiology: Case Study from Houston, Texas

Abstract: This study represents an example of investigating the associations between the joint exposure to ozone (O3) and particulate matter of sizes less than or equal to 2.5 micrometers in aerodynamic diameter (PM2.5) and cardiovascular disease (CVD) emergency room (ER) visits and chronic obstructive pulmonary disease (COPD) ER visits using multivariate geostatistics in Houston, Texas, from 2004 to 2009. Analyses showed lack of strong pair-wise association among the predictors of O3, PM2.5, wind speed, relative humidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Ordinary least squares with spatial dependence regression analyses were conducted. Spatial weights matrix was formed using wells longitude and latitude data [11] [29]- [31]. The spatial regression performed has the equation [Cl] = intercept + longitude + latitude +distance to the Gulf of Mexico + sea level + groundwater withdrawals + spatial residual.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ordinary least squares with spatial dependence regression analyses were conducted. Spatial weights matrix was formed using wells longitude and latitude data [11] [29]- [31]. The spatial regression performed has the equation [Cl] = intercept + longitude + latitude +distance to the Gulf of Mexico + sea level + groundwater withdrawals + spatial residual.…”
Section: Methodsmentioning
confidence: 99%
“…These lead to socioeconomic effects including displacement, evacuations, and public health issues. These impacts combined with other issues facing coastal communities in Texas and other places in the world, makes it more complicated to mitigate and manage the issues [11]- [18]. Disparity of impacts affect groups of lower income, non-English speakers, and vulnerable age groups (65 years or older, 5 years or younger) [14].…”
mentioning
confidence: 99%
“…Although O 3 in the stratosphere benefits life on Earth by filtering out harmful ultraviolet radiation from the sun, O 3 and PM 2.5 can have adverse effects on human health on the ground. The level of simultaneous exposure Atmosphere 2024, 15,198 2 of 23 to PM 2.5 and O 3 is highly correlated with an increased risk to human health, including cardiovascular and respiratory diseases [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies focusing on the impact of socioeconomic status (SES) on asthma have demonstrated varying degrees of associations with factors like income, college education attainment, and living in urban or rural areas. These associations varied with demographic factors such as age and ethnicity [5] [7] [12] [13]. The effect of SES on asthma morbidity and mortality is attributed to factors such as living conditions, working environment, proximity to air pollutant discharge, and psychosomatic stress [7] [14].…”
Section: Introductionmentioning
confidence: 99%